1994
DOI: 10.1007/bf01744490
|View full text |Cite
|
Sign up to set email alerts
|

Use of nitroglycerin for the treatment of acute myocardial infarction

Abstract: After a decade of warnings against the use of nitrates in acute myocardial infarction (MI), they are becoming recognized for their potential to salvage left ventricular (LV) myocardium, geometry and function. Low-dose intravenous (IV) nitroglycerin (NTG) infusion for the first 48 h after acute MI, titrated to lower mean blood pressure by 10% to 30%, but not below 80 mmHg, has been shown to be safe, to improve hemodynamics, and to decrease infarct size, infarct expansion, complications, and deaths in a prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
(135 reference statements)
0
2
0
Order By: Relevance
“…[11][12][13] In our study, NTG given in a manner that recapitulates the clinical setting, i.e. at the end of the ischaemia and during reperfusion, at a dose which does not affect the haemodynamic parameters 34 reduced infarct size in mice and rabbits. The divergent results between previous studies and our work may be due to (i) the observed haemodynamic instability, 12 which suggests a progressive decline of left ventricular function and (ii) the dosing protocol, 13 in which a constant rate of 50 mLÁh -1 for 65 min was used.…”
Section: Discussionmentioning
confidence: 76%
“…[11][12][13] In our study, NTG given in a manner that recapitulates the clinical setting, i.e. at the end of the ischaemia and during reperfusion, at a dose which does not affect the haemodynamic parameters 34 reduced infarct size in mice and rabbits. The divergent results between previous studies and our work may be due to (i) the observed haemodynamic instability, 12 which suggests a progressive decline of left ventricular function and (ii) the dosing protocol, 13 in which a constant rate of 50 mLÁh -1 for 65 min was used.…”
Section: Discussionmentioning
confidence: 76%
“…NTG minimizes myocardial infarction in vivo in dogs 247 , whilst it has not been proved to be cardioprotective when it is administered during ischemia in anesthetized pigs 245 and rabbits 246 . In our study, NTG given at the end of the ischemia and during reperfusion, at a dose which does not change haemodynamic parameters, thus, reflecting the routine clinical practice 362 , reduces infarct size in anesthetized rabbits and mice. The divergent results between the others and the present study may be due to i) the observed haemodynamic instability in the study of Liu et al 245 ., which suggests a progressive decline of LV function upon NTG administration in their model and ii) dosage protocol in the latter study of Salloum et al 246 ., in which a constant rate of 50 ml/hr for 65 min was used.…”
Section: Discussionmentioning
confidence: 55%